Metodología para identificación y valoración del riesgo en dinámica gráfica Ltda (2021)
The subject of this research is: methodology for risk identification and assessment at Dinámica Grafica Ltda. The main objective is to develop the matrix that allows the identification of hazards and mitigates the implementation of controls to mitigate occupational risks at Dinámica Grafica Ltda., in order to reduce workplace accidents and comply with current legal regulations, which encompass the entire organization, whether administrative or operational. The most important and identified findings within the 23 processes, which were valued in equal numbers. In turn, within the printing and die-cutting area it represents a significant percentage of the observed hazards. Finally, 206 intervention measures are proposed to reduce and control hazards and risks, within the Occupational Health and Safety System at Dinámica Grafica Ltda.